2022
DOI: 10.3390/nu14194084
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Palmitoylethanolamide on Pain Intensity, Central and Peripheral Sensitization, and Pain Modulation in Healthy Volunteers—A Randomized, Double-Blinded, Placebo-Controlled Crossover Trial

Abstract: Palmitoylethanolamide (PEA) is marketed as a “dietary food for special medical purposes”. Its broad-spectrum analgesic, anti-inflammatory, and neuroprotective effects make PEA an interesting substance in pain management. However, the underlying analgetic mechanisms have not yet been investigated in humans. The aim of our study is to provide a deeper understanding of the involved mechanisms, which is essential for differentiating therapeutic approaches and the establishment of mechanism-based therapeutic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…However, recent meta-analyses have provided evidence for the efficacy of PEA in the treatment of inflammation and neuropathic pain [ 14 , 38 ]. Data from healthy volunteers has also shown that PEA is capable of reducing central sensitization and moderating pain modulation [ 12 ], which are desirable features for chronic pain treatments and are consistent with observations from our included studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, recent meta-analyses have provided evidence for the efficacy of PEA in the treatment of inflammation and neuropathic pain [ 14 , 38 ]. Data from healthy volunteers has also shown that PEA is capable of reducing central sensitization and moderating pain modulation [ 12 ], which are desirable features for chronic pain treatments and are consistent with observations from our included studies.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, our group published the results of a randomized crossover study demonstrating clinically relevant analgesic properties of PEA. We used a model of thermal pain, thus investigating its effects on peripheral and central nociceptive mechanisms and on pain modulation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…PEA was found to be a mechanism of action that includes mast cells and basophils and has been proven to exhibit a neuroprotective effect in cerebellar granule cells [ 127 ]. However, taking into account the pathophysiology of NcplP and the cannabimimetic actions of PEA, it is likely to be worth investigating whether PEA will elicit analgesia [ 127 , 128 , 129 ]. In addition to that, PEA was shown to suppress inflammation [ 127 , 129 , 130 ].…”
Section: Primarily Clinical Trialsmentioning
confidence: 99%
“…in the thalamus. This process is called central sensitization [ 4 , 5 ]. Sensitization, on the one hand, is generally understood to be a physiological, adaptive, self-limiting process that aids in the healing of injuries.…”
Section: Introductionmentioning
confidence: 99%